1993
DOI: 10.1099/00221287-139-12-3225
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and specific detection of the thermostable direct haemolysin gene in Vibrio parahaemolyticus by the polymerase chain reaction

Abstract: Synthetic oligonucleotide primers derived from a sequence of the thermostable direct haemolysin (tdh) gene were used in a polymerase chain reaction (PCR) amplification technique to detect this gene in strains of Vibvio pavahaemolyticus. A total of 36 TDH-producing, and 89 TDH-negative Vibvio pavahaemolyticus strains and 46 other vibrios and enteric pathogens were studied. In all, 36 strains of Vibrio pavahaemolyticus from which the tdh gene could be successfully amplified by PCR were found to be TDH-positive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…Many studies have demonstrated that virulent strains of V. parahaemolyticus possess either the gene tdh or trh, or both 21 . The evidence of transmission of these genes through plasmids or insertion elements has already been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that virulent strains of V. parahaemolyticus possess either the gene tdh or trh, or both 21 . The evidence of transmission of these genes through plasmids or insertion elements has already been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Polymerase chain reaction (PCR) methods to detect the presence of these genes have been developed (Tada et al . 1992; Lee and Pan 1993; Karunasagar et al . 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Total DNAs from 11 different V parahaemolyticus strains were isolated and digested with EcoRI, and Southern blots were prepared by using alkaline transfer. All hybridizations were performed under stringent conditions at 65 C. The hybridization results showed that all of the strains had an EcoRI fragment of about [13][14][15][16][17][18] Kb that hybridized with the pR72H probe (Fig. 2).…”
Section: Conservation Of Pr72h Fragment Among V Parahaemolyticusmentioning
confidence: 99%